Ammonite biostratigraphy of the jurassic of Tanzania - Kapilima, S (Tanzania Journal of Science, 2021)
The present paper summarizes the previous biostratigraphical researches and incorporates the recent research findings on the Jurassic rocks in the coastal basin of Tanzania. The ammonites used for the biostratigraphical classification are from two sub-basins along the coastal belt of Tanzania: Mandawa (south) and Ruvu- Tanga (north). The oldest known ammonites from these basins are of Aalenian age. The biostratigraphical classification of the Jurassic sequence, on the basis of the vertical and horizontal distributions of the ammonite assemblages, permits the erection of eight sub stages of Jurassic: Upper Aalenian (Concavum-Zone), Bajocian (Humphrieasianum-Zone), Middle Callovian (Coronatum-Jason Zone), Upper Callovian (Lamberti-Athleta Zone), Lower Oxfordian (Cordatum-Mariae Zone), Middle Oxfordian (Transversarium-Zone), Lower Kimmeridgian (Tenuilobatus-PlatinotaZone)and Upper Kimmeridgian-Tithonian (Beckeri-Zone). This fauna assemblage forms an intergral part of the Indo-Madagascar Province and the Trans-Erythraean-Trough.